(3QSGdI aj GdSjQI hGdehdO GdfHhjs - (3CMeO Hf jhSa Hf eGdc GdQYjfj GdZQfGWj GdCfOdSj, CHh LYaQ , J (B779 (3g` s
(3ChdgG (B:s
(3CeG HYO ,aEf fHjfG eMeOkkG Udi Gddg Ydjg hSde aNQ GdhLhO s
(3BNQgG (B:s
(3Gddge ceG CQSdJg QMeI ddYGdejf aGLYdfG HSfJg GdTQjaI YGedjf hUdi Gddg Ydi SjOfG eMeO hBdg GdWjHjf GdWGgQjf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B11 - (3U(B21s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B213s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B201 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs